Eine umstrittene Altarinschrift aus Vindobona - Alföldy, Géza (Tyche, 2011)
New reading of CIL III 14359,27 found 1899 in Vindobona (Vienna). The altar was dedicated to Iupiter, Neptunus Augustus, Salacia, the Nymphs, the river Acaunus (which is today the river Wien) and to all the other gods and goddesses by the soldiers of a detachment of the legio VIII Augusta which was named here VII pia VII fidelis. The date of the erection of the monument was between 4th April and 15th Mail 268. A relief seems to represent Neptun as Danube who steps on a bearded man with horns symbolizing the barbarians. The altar was installed at the estuary of the river Wien into the Danube probably showing the special meaning for the vexillatio, e.g. remembering a victory over the barbarians.